The Influence Of Product Quality, Price, And Brand Image On Consumer Loyalty Mediated By Consumer Satisfaction (Empirical Study: Consumers Of Kacang Kulit Dua Kelinci In Jakarta) - Kelvin Kelvin; Liem Bambang Sugiyanto (Journal Research of Social Science, Economics, and Management, 2023)
This research aims to determine how product quality, price, and brand image influence consumer loyalty in consuming Kacang kulit Dua Kelinci, mediated by Consumer Satisfaction. This research uses a quantitative approach. The survey was conducted on 180 respondents who had consumed the Kacang kulit Dua Kelinci in the province of DKI Jakarta. Data analysis was performed using the Structural Equation Model (SEM) AMOS. The research results show that the price of Kacang kulit Dua Kelinci has a strong relationship and a significant influence on consumer loyalty in consuming Kacang kulit Dua Kelinci in DKI Jakarta province. Different from product quality and brand image, which do not have a strong relationship and significant influence on consumer loyalty in consuming Kacang kulit Dua Kelinci. However, product quality, price, and brand image significantly influence consumer loyalty when mediated by consumer satisfaction. The research results also show that, in total, price is the most significant contributor to consumer loyalty, followed by product quality as the second largest contributor, then brand image as the most minor contributor. This conclusion shows that the Kacang kulit Dua Kelinci industry can maximally increase consumer loyalty by increasing consumer satisfaction so that consumers become loyal to continue consuming Kacang kulit Dua Kelinci. The limitation of the research is that the respondents collected only live in DKI Jakarta and focused on one product from the Dua Kelinci brand, Peanut Shell.